Microsoft Office 2007 on demand - Johnson, Steve, 1961- (Que, 2006)
How to Use - Office: Organize information and add impact with clip art, SmartArt diagrams, tables, and charts with a new results-oriented interface - Word: Create great-looking documents faster using themes, styles, and templates - Excel: Use organizing, processing, and presenting tools to create data in Excel - PowerPoint: Create powerful presentations faster using ready-made design templates and themes - Outlook: Use tools for creating and managing your e-mail, calendar, contacts, and tasks - Publisher: Use task panes to quickly create a brochure or a newsletter without being a designer - SharePoint: Collaborate and share documents and information - Prepare for the Microsoft Certified Application Specialist exam - Practice your new skills with the useful workshops inside On the Web This book uses real-world examples to give you a context in which to use a task. This book also includes workshops to help you put together individual tasks into projects. The Office example files that you need for project tasks are available at www.perspection.com Perspection has written and produced books on a variety of computer software-including Microsoft Office 2003 and XP, Microsoft Windows XP, Apple Mac OS X Panther, Adobe Photoshop CS2, Macromedia Flash 8, Macromedia Director MX, and Macromedia Fireworks-and Web publishing. In 1991, after working for Apple Computer and Microsoft, Steve Johnson founded Perspection, Incorporated Perspection is committed to providing information and training to help people use software more effectively. Perspection has written more than 80 computer books, and sold more than 5 million copies. Includes MCAS Exam Objectives! This courseware meets the objectives for the Microsoft Certified Application Specialist (MCAS). Upon completion of this courseware, you may be prepared to take the exam for MCAS qualification. To learn more about becoming a Microsoft Certified Application Specialist, visit www.microsoft.com. Chapter 1 Getting Started with Office 1 Chapter 2 Using Shared Office Tools 33 Chapter 3 Adding Art to Office Documents 57 Chapter 4 Adding Shapes to Office Documents 93 Chapter 5 Formatting Office Documents 115 Chapter 6 Creating a Document with Word 131 Chapter 7 Formatting a Document with Word 153 Chapter 8 Enhancing a Document with Word 173 Chapter 9 Creating a Worksheet with Excel 211 Chapter ...